ANALISIS INDIKASI FREE-RIDING PADA REAKSI PASAR SUATU SAHAM DALAM HUBUNGANNYA DENGAN PENGUMUMAN LAPORAN KEUANGAN PERUSAHAAN LAIN (EVENT STUDY PADA INDEKS LQ45) - Wijijayanti, Trisetia; Wiliandri, Ruly (IQTISHODUNA, 2015)
This research was purposed to examine whether there was free-riding on market reaction of a sharein correlation with the announcement of other companies’ financial report. The sample of this research wereindex LQ45 emiten who announced audited financial report in 2011 period of February–July 2012. By applyingpurposive sampling method, it was obtained 30 companies to be the objects of this research. Data used in thisresearch were LQ45 emiten who announced financial report period February–July 2012, financial data weretaken from Indonesian Capital Market Directory, and other supporting data resources. The analytical toolused in this research was t test. From the result of data analysis and discussion, it could be concluded thatthere was free-riding indication on market reaction of a share in correlation with the announcement of othercompanies’ financial report (event study on Index LQ45). It could be proven by number of t calculation (-1,599) t table (-1,316).